Kenali dan Waspadai Amnesia Fugu Disosiatif - Almaira Aura Zahra; Siska Nabila; Wahyu Aulizalsini Alurmei (Jurnal Sains Farmasi Dan Kesehatan, 2024)
Dissociative disorders are conditions characterized by partial or complete loss of past memories, consciousness that causes changes in identity, and control over body movements. There are four types of dissociative disorders: dissociative amnesia, dissociative fogginess, dissociative identity disorder, and depersonalization disorder. Assessment methods that can be carried out include observation, interviews and psychological tests. Psychoanalytic therapy, psychotherapy, cognitive therapy, family therapy, and creative therapy were identified as effective intervention methods. The aim of this research is to understand theory and identify effective intervention methods in treating dissociative disorders. The research method used is a literature study method by looking for references relevant to the case or problem. One of the cases discussed was a civil servant in Pringsewu, Lampung, who experienced dissociative fugue disorder and was missing for 20 days. Appropriate treatment can help sufferers overcome this disorder and integrate their personality.